2008
DOI: 10.1172/jci35798
|View full text |Cite
|
Sign up to set email alerts
|

Insertional mutagenesis combined with acquired somatic mutations causes leukemogenesis following gene therapy of SCID-X1 patients

Abstract: X-linked SCID (SCID-X1) is amenable to correction by gene therapy using conventional gammaretroviral vectors. Here, we describe the occurrence of clonal T cell acute lymphoblastic leukemia (T-ALL) promoted by insertional mutagenesis in a completed gene therapy trial of 10 SCID-X1 patients. Integration of the vector in an antisense orientation 35 kb upstream of the protooncogene LIM domain only 2 (LMO2) caused overexpression of LMO2 in the leukemic clone. However, leukemogenesis was likely precipitated by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
910
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,124 publications
(957 citation statements)
references
References 39 publications
14
910
0
13
Order By: Relevance
“…The observation that the internal transgene promoter was not necessary for the increase in tumor incidence is corroborated with a more recent study that noticed the same effect when even only a portion of the viral ITR was integrated [80]. The fact that a region of some rAAV2 ITRs contains a bidirectional binding site for a strong liver-specific transcription factor (HNF1α) aids the speculation that unforeseen integration of AAV ITRs can influence the expression of neighboring genes, similar to the situation observed following retroviral integration [72,81]. It is important to acknowledge, however, that larger animal models have not presented with rAAV-associated HCC and that so far no similar cancers have been reported in the numerous rAAV liver gene therapy clinical trials that have been undertaken [82,83].…”
Section: A Brief History Of In-vivo Gene Therapysupporting
confidence: 54%
See 1 more Smart Citation
“…The observation that the internal transgene promoter was not necessary for the increase in tumor incidence is corroborated with a more recent study that noticed the same effect when even only a portion of the viral ITR was integrated [80]. The fact that a region of some rAAV2 ITRs contains a bidirectional binding site for a strong liver-specific transcription factor (HNF1α) aids the speculation that unforeseen integration of AAV ITRs can influence the expression of neighboring genes, similar to the situation observed following retroviral integration [72,81]. It is important to acknowledge, however, that larger animal models have not presented with rAAV-associated HCC and that so far no similar cancers have been reported in the numerous rAAV liver gene therapy clinical trials that have been undertaken [82,83].…”
Section: A Brief History Of In-vivo Gene Therapysupporting
confidence: 54%
“…This is especially true in diseases where the therapeutic gene can give a proliferative advantage, such as SCID, and/or where insertion of an active transcriptional unit (at least a promoter and transgene) can interfere with neighboring genes that perturb the regulation of cell division, leading to either hypo- or hyper-proliferation [81]. It is likely that this insertional mutagenic effect is more profound in cells with high proliferating potential such as stem or progenitor cells.…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…The recognized safety concerns of integrating viral vectors, 51 for both fetus and mother, must be addressed before clinical application. Furthermore, it remains to be determined whether lentiviral gene transfer to the fetal lung achieves life-long and therapeutic levels of transduction.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60] These hematological disorders were attributed to the so-called insertional mutagenesis which means that the promoter driving the transgenes influences the expression of genes in the host genome in the vicinity of the integrated provirus. Although intense analyses revealed that additional genomic instabilities were involved in the progression of these leukemic clones, 61,62 further vector improvement is urgently needed. One advantage of lentiviral vectors is their substantially reduced genotoxic risk compared with gammaretroviral vectors.…”
Section: Discussionmentioning
confidence: 99%